Mapping of Flood Inundation and Eco-hydraulic Analyses to Minimize Food Discharge in Tributaries - Ziana Ziana; Azmeri Azmeri; Alfiansyah Yulianur; Ella Meilianda; Mubarak Mubarak (Graduate Program of Syiah Kuala University, 2023)
Eco-hydraulic analyses begin with the arrangement of tributaries. This research aimed to minimize the discharge of flood run-off downstream and map the flood inundation by spatial analysis uses DEMNAS data and mapping of flood inundation areas using ArcGIS. Analysis of return period flood points using HEC-RAS version 5.0.7. The data needed is the cross section of the river, the distance between the sections, the Manning's roughness number, the return period flood discharge and the slope of the river. The integration between topographic maps, watersheds and flood water levels can display areas that are potentially affected by inundation floods, so that the flood inundation limits and flood inundation areas can be calculated. This research examined proper eco-hydraulics design so that it could reduce discharge, identify locations prone to flooding, and describe the magnitude of the flood impact quantitatively. The results eco-hydraulic method obtained the design border width of 100 m, the condition before the existing river border arrangement was carried out, the inundation height was 0.30 – 1.13 m and after the river border arrangement the discharge could be reduced to 113.09 – 209 m3/s and the inundation height is 0 – 0.31 m. Based on the research results, it is known that border arrangement can provide benefits for flood control measures.